Preparation method of vacuum extrusion molding granules for fish culture feed or auxiliary compound feed by using livestock blood, wheat amphibole and detoxified calcium - GUO DUOEN; GUO CHENGGEN (2024)
The invention relates to a preparation method of vacuum extrusion molding particles for fish-farming feed or auxiliary compound feed by using livestock blood, wheat amphibole and detoxified calcium. According to the present invention, citric acid, wood vinegar, sodium chloride, a yucca extract, nano-silver and zirconium are added and mixed to livestock blood to prepare a first mixture, bentonite and zeolite are prepared and mixed with the first mixture, calcined detoxified calcium and mineral powder, and then vacuum extrusion molding and dry heat drying (200-500 DEG C) are performed for 15-40 min so that the moisture content is less than 12%, the composition can be mass-produced, slow in disintegration of dosage forms, and excellent in storage properties, and can satisfy conditions such as satiety increase and weight gain increase of a feeding subject. 本发明涉及利用家畜血液、麦闪石、脱毒钙的养鱼饲料用或配合饲料辅助用真空挤出成型颗粒制备方法。在本发明中，向家畜血液中添加及混合柠檬酸、木醋液、氯化钠、丝兰提取物、纳米银、锆来制备第一次混合物，准备膨润土、沸石并与上述第一次混合物、煅烧脱毒钙、矿物粉末混合之后进行真空挤出成型、干热干燥(200～500℃)15～40分钟